2005
DOI: 10.1074/jbc.m501716200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Protein Kinase Cγ Found in Spinocerebellar Ataxia Type 14 Is Susceptible to Aggregation and Causes Cell Death

Abstract: Spinocerebellar ataxia type 14 (SCA14) is an autosomal dominant neurodegenerative disease characterized by various symptoms including cerebellar ataxia. Recently, several missense mutations in the protein kinase C␥ (␥PKC) gene have been found in different SCA14 families. To elucidate how the mutant ␥PKC causes SCA14, we examined the molecular properties of seven mutant (H101Y, G118D, S119P, S119F, Q127R, G128D, and F643L) ␥PKCs fused with green fluorescent protein (␥PKC-GFP). Wild-type ␥PKC-GFP was expressed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 46 publications
3
72
1
Order By: Relevance
“…Although we have shown that most of the SCA14 mutant ␥PKCs have increased basal kinase activities, several mutations actually have lower or unchanged activities (48). In contrast to controversial results concerning the kinase activity of mutant ␥PKC, we confirmed that most of the mutant ␥PKCs found in SCA14 tend to form aggregates (19). Furthermore, we and another group have recently demonstrated that the aggregation of mutant ␥PKC triggers apoptosis by impairing the ubiquitin proteasome system and inducing endoplasmic reticulum stress (21,49).…”
Section: Pcsupporting
confidence: 45%
See 3 more Smart Citations
“…Although we have shown that most of the SCA14 mutant ␥PKCs have increased basal kinase activities, several mutations actually have lower or unchanged activities (48). In contrast to controversial results concerning the kinase activity of mutant ␥PKC, we confirmed that most of the mutant ␥PKCs found in SCA14 tend to form aggregates (19). Furthermore, we and another group have recently demonstrated that the aggregation of mutant ␥PKC triggers apoptosis by impairing the ubiquitin proteasome system and inducing endoplasmic reticulum stress (21,49).…”
Section: Pcsupporting
confidence: 45%
“…Immunoblotting and Chase Assay-Cells on 6-cm-diameter dishes were analyzed by immunoblotting using an anti-GFP antibody as described previously (19). Briefly, cells were lysed in radioimmune precipitation assay buffer (1% Nonidet P40, 0.1% sodium deoxycholate, 0.1% SDS, 150 mM NaCl, 1 mM EDTA, 20 g/ml leupeptin, 1 mM phenylmethanesulfonyl fluoride (PMSF), 1 mM sodium orthovanadate, 1 mM NaF, 100 nM Calyculin A and 10 mM Tris/HCl, pH 7.4) by sonication (UR-20P, TOMY SEIKO, Tokyo; output, 4; duty, 50%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PKCγ acts as an oxidative stress sensor to prevent the lens from oxidative damage through proper control of gap junctions. It has been reported recently that missense mutations in PKCγ cause the dominant spinocerebellar ataxia type 14 (SCA14), a neurodegenerative disorder with onset age as early as three years (Chen et al, 2003, 005;van de Warrenburg et al, 2003;Stevanin et al, 2004;Yabe et al, 2003, Verbeek et al, 2005Seki et al, 2005;Alonso et al, 2005;Klebe et al, 2005;Vlak et al, 2006;Fahey et al, 2005). Most of the PKCγ SCA14 mutations occur in the C1B subdomain.…”
Section: Introductionmentioning
confidence: 99%